The Competitiveness Advantage of Enterprises : A Decision Strategy - Fahlefi, Diva Riza; Indriani, Farida (Universitas Negeri Semarang, 2021)
In today's globalized world, trade has become increasingly complex. The dependence that grows between markets and increasing competition makes it increasingly difficult to defend a company's market position. It is increasingly difficult for companies to maintain their competitive advantage. Therefore, companies need to make a strategy for their position and build a competitive advantage (Competitive Advantage). The company must be able to make the best use of its strengths and must meet customer needs to achieve a competitive advantage that will facilitate the elimination of competition and gain large profits. SWOT analysis can be used to find the competitive advantage of a company. The method used in this study is a SWOT analysis. The result of this research shows that companies in quadrant I can implement aggressive or SO strategies. This strategy is in the form of utilizing the abilities and skills of good employees to create unique new products, improve company facilities that are in strategic places, and improve service to customers so that they are more familiar.